I.iv.4. Sequence of copy letter books of John Pitt Kennedy's correspondence concerning Ireland - Kennedy, John Pitt, 1796-1879; Larcom, Thomas A. (Thomas Aiskew), 1801-1879; Devon, William Courtenay, Earl of, 1777-1859; Fortescue, Hugh Fortescue, Earl, 1783-1861; Moore, James, fl. 1834-1864; Doherty, James W., fl. 1847-1848; Kennedy, Charles Horatio, 1810-1862; Kennedy, Evory, 1806-1886.; Kennedy, Tristram; Style, Charles, 1777-1853; Style, William, 1785-1868; Napier, Charles James, 1782-1853; et al. (1836)
Fourteen copy letter books containing John Pitt Kennedy's correspondence, mainly concerning Irish affairs, including reference to land reform, poor relief, military defence, education and corruption. Also includes some family correspondence, sketches and personal memoranda.
The books are numbered as part of a sequence, but not all of the volumes are among this collection. Contains volumes 1-4 and 8-15. Two further books in folder 6 are not clearly numbered.
Keywords: Landlord and tenant -- Ireland; Education -- Ireland -- 19th century; Ireland -- History -- Famine, 1845-1852; Ireland -- Military policy